Environmental Quality Factors with The Incidence of Pulmonary Tuberculosis: A Literature Review - Hanung Nurany; Mursid Raharjo; Mateus Sakundarno Adi (Fakultas Teknik, 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that can attack the lungs and other organs. Tuberculosis (TB) is still a global priority health problem because Indonesia is one of the countries with the highest number of TB cases in the world. It is estimated that around 845.000 Indonesians in 2019 suffer from tuberculosis. Around 92,700 people die from TB in Indonesia per year. The purpose of this study was to determine the environmental risk factors with the incidence of pulmonary tuberculosis (TB). The method in this study uses the literature review method by selecting data sources according to the desired topic and criteria. The data base used in the search for sources is Google Scholar, ejournal.undip.ac.id, and Portal Garuda, with the keywords pulmonary tuberculosis, TB incidence factors, tuberculosis environmental factors, and the physical condition of the TB patient's house. The results of studies from 10 scientific journals on environmental risk factors for TB disease show that ventilation area, occupancy density, lighting intensity, humidity and room temperature are risk factors for TB incidence.